2017
DOI: 10.1002/14651858.cd012423
|View full text |Cite
|
Sign up to set email alerts
|

Training healthcare providers to respond to intimate partner violence against women

Abstract: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows:To assess the effectiveness of training programmes that seek to improve healthcare providers' identification of, and response to, IPV against women.1 Training healthcare providers to respond to intimate partner violence against women (Protocol)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 47 publications
1
21
0
2
Order By: Relevance
“…DV training programs aim to increase midwives' understanding of DV as well as providing knowledge and skills to respond appropriately to women. 18 The DV program offered in this study was multifaceted and aimed to not only promote midwives' abilities to conduct routine enquiry, and sensitively support women who disclose violence; but also improve workplace policies and processes. In line with previous findings, the current study demonstrated that robust educational programs can support midwives to undertake this role.…”
Section: Discussionmentioning
confidence: 99%
“…DV training programs aim to increase midwives' understanding of DV as well as providing knowledge and skills to respond appropriately to women. 18 The DV program offered in this study was multifaceted and aimed to not only promote midwives' abilities to conduct routine enquiry, and sensitively support women who disclose violence; but also improve workplace policies and processes. In line with previous findings, the current study demonstrated that robust educational programs can support midwives to undertake this role.…”
Section: Discussionmentioning
confidence: 99%
“…The module provided guidance for integrating the knowledge into the patient care process as well as encouraging learners to take responsibility for their own learning by guiding the participants to seek out referral resources within their own communities, identify their associated state laws, and develop protocols for IPV disclosures in their practice environment. Module content was guided by three key resources—the National Consensus Guidelines on Identifying and Responding to Domestic Violence Victimization in Health Care Settings, the health professional competencies need for addressing exposure to violence and abuse developed by the Academy on Violence and Abuse, and the existing training materials available in other health professions [ 31 , 40 , 41 , 42 , 43 ]. The module’s learning objectives included: Increase knowledge and awareness of intimate partner violence (IPV).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, healthcare professionals should understand the vulnerabilities that women facing violence may experience, including increased risk to HIV, and ensure that testing and treatment are encompassed within the healthcare plan (United Nations AIDS 2019). Furthermore, healthcare staff should inquire about children or other dependents who may be facing abuse and offer the same support and services to ensure the safety of these vulnerable populations (Kalra et al 2017). However, the lack of comprehensive intimate partner violence training for healthcare providers in the education and clinical setting imposes a barrier for healthcare providers to adequately fulfill their roles.…”
Section: Economic Costs Of Intimate Partner Violence On the Healthcarmentioning
confidence: 99%